THE ROLE OF WHATSAPP META AI IN ENHANCING PSYCHOLOGICAL CAPITAL AMONG UNIVERSITY STUDENTS - Dr. Leenah Ãskaree; Soha Sohail; Shiza Javed; Turfa Aziz; Sarah Zulfiqar; Aisha Zulfiqar (Policy Research Journal, 2025)
This study examines the impact of WhatsApp Meta Artificial Intelligence (AI) on university students' psychological capital (PsyCap), a construct comprising self-efficacy, optimism, hope, and resilience. WhatsApp Meta AI was selected as the focal platform due to its popularity among students and features such as real-time feedback, task management, and emotional support, which align closely with PsyCap components. The research utilized a quantitative methodology, collecting data from university students through validated instruments designed to measure WhatsApp Meta AI usage and the dimensions of PsyCap. Participants were recruited using convenience sampling and snowball sampling technique to ensure accessibility within the demographic. Analysis through descriptive statistics, correlation tests, and regression analysis revealed a substantial positive relationship between WhatsApp Meta AI usage and PsyCap levels, particularly in enhancing self-efficacy and optimism, followed by hope and resilience. This study outlines critical implications for educational practices, acknowledges its limitations, such as sample size and self-report biases, and provides avenues for future research to explore AI’s role in academic and psychological resilience.